1983
DOI: 10.1073/pnas.80.11.3255
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies to renal brush border membrane maltase: age-associated antigenic alterations.

Abstract: Monoclonal antibodies to maltase (a-D-glucoside glucohydrolase, EC 3.2.1.20) from young adult and aged rats were prepared by the hybridoma technique. Four cell lines producing antibodies of the IgGI subclass to maltase were established. Two, designated IF12E1 and 8B1G6, produced monoclonal antibodies specific for the catalytically active form of the enzyme found predominantly in enzyme preparations from young animals. The other two clones designated 7G1OH3 and 2E1C1O produced monoclonal antibodies that react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1984
1984
2002
2002

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…Recognizes both gp330 and maltase (by immunoprecipitation) . FIGURE 14 Immunogold localization of gp330 to several coated pits (cp) on glomerular epithelial cells . Clusters of protein A-gold are found in three coated pits located on the sides of the foot processes .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recognizes both gp330 and maltase (by immunoprecipitation) . FIGURE 14 Immunogold localization of gp330 to several coated pits (cp) on glomerular epithelial cells . Clusters of protein A-gold are found in three coated pits located on the sides of the foot processes .…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal antibodies directed against gp330 (the Heymann nephritis antigen) were obtained from clone D 1551`21 (IgG2 subclass) (13) and those for active maltase from clone 1F12G1 (IgG, subclass) . IgG was purified from ascites by ammonium sulfate precipitation followed by ion-exchange chromatography on DEAE-Biocel A (15) or by affinity chromatography on a Protein A-Sepharose 4B column (14).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, Sharma and Rothstein 96 demonstrated that the young and old forms of the glycolytic enzyme enolase (isolated from young and old nematodes, respectively), which display different activities, share the same amino acids sequence; however, when these two enzyme species were unfolded by guanidine:HCl (a strong denaturant of proteins) and then allowed to refold, they formed an identical structure similar to that of old enolase. Strong evidence was also found for conformational modifications as the origin of the observed aging effects in rat kidney maltase 33 and in rat muscle GAPDH 27 . None of these studies, however, provided direct, conclusive, evidence that there were no other changes in the old forms of these proteins and, hence, that purely conformational alterations were indeed responsible for the effects seen.…”
Section: Conformational Alterations and Aggregationmentioning
confidence: 90%
“…These modifications have been found to involve the functional properties, the stability, as well as the structural integrity of these proteins. Old proteins (i.e., those found in tissues of old animals) often, though not always, display a reduction in their biological activity, 26–28 a modified heat inactivation pattern reflecting alterations in their stability, 29–31 and frequently possess a modified affinity to antibodies raised against the young form of the protein, a reflection of changes in structural integrity 32,33 . The fact that, as a rule, those proteins whose activity is affected by aging, display reduced (rather than enhanced) biological competence is not surprising as evolution has strongly selected for each protein a structure that possesses a high biological activity, and a change in the former is likely to reduce the latter.…”
mentioning
confidence: 99%
“…Glyceraldehyde 3-phosphate dehydrogenase and pyruvate kinase, also have catalytically inactive isoforms during aging (Dovrat et al, 1984;Hopkirk and Bloxham, 1979). Ornithine decarboxylase in the mouse brain (Laitinen, 1985), as well as maltase (Reiss and Sacktor, 1983), and glucose 6-phosphate dehydrogenase (Dovrat et al, 1986) are other examples of inactive isoenzymes that could be part of cell structures.…”
Section: Ck Isoenzyme Transition In the Rat Encephalonmentioning
confidence: 99%